2018
DOI: 10.21451/1984-3143-ar2018-0061
|View full text |Cite
|
Sign up to set email alerts
|

History, origin, and function of transzonal projections: the bridges of communication between the oocyte and its environment

Abstract: Development and differentiation of a functional oocyte that following fertilization is able to give rise to a new individual requires continuous physical contact with the supporting somatic cells of the ovarian follicle. As the oocyte is surrounded by a thick extracellular coat, termed the zona pellucida, this essential contact is mediated through thin cytoplasmic filaments known as transzonal projections (TZPs) that project from the somatic granulosa cells adjacent to the oocyte and penetrate through the zona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…1) In vivo growing oocytes collected from early antral follicles (0.5-0.7 mm) and fully grown oocytes collected from antral follicles (4-6 mm). 2) DOs collected from early antral follicles cultured for 12 and 24 hours. 3) DOs cocultured with MGCs 24 hours after denudation, for 24-120 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) In vivo growing oocytes collected from early antral follicles (0.5-0.7 mm) and fully grown oocytes collected from antral follicles (4-6 mm). 2) DOs collected from early antral follicles cultured for 12 and 24 hours. 3) DOs cocultured with MGCs 24 hours after denudation, for 24-120 hours.…”
Section: Discussionmentioning
confidence: 99%
“…1) DOs collected from early antral follicles cultured for 24 hours. 2) DOs cultured with MGCs hours after denudation, for 13 days and OCGCs cultured for 14 days. 3) In vivo fully grown oocytes collected from antral follicles (4-6 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes and cumulus cells communicate bilaterally, thereby promoting oocyte growth. Previous studies have suggested that this communication is mediated by paracrine signals and gap junctions existing at the end of transzonal projections (TZPs) as well as extracellular vesicles [ 18 , 19 , 20 ]. Thus, it is assumed that the connections between oocytes and cumulus cells are maintained during in vitro growth culture.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the intimate relationship between the oocyte and cumulus cells has been investigated to better define the role of TZPs [ 76 , 77 ]. Although more research needs to be done to determine how the physiology, distribution and retraction of TZPs impacts IVEP outcomes in both prepubertal and adult oocytes, TZPs are known to facilitate communication and the transport of essential molecules between granulosa cells and the oocyte [ 76 , 78 ]. Despite differences observed in the organization of TZPs in COCs from lambs compared to adult ewes, the impact on embryo development remains unclear [ 79 ].…”
Section: Understanding Developmental Competence Of Oocytesmentioning
confidence: 99%